Kesadaran akan Allah di dalam Dinamika Religiusitas Manusia menurut Perjanjian Lama - Hery Susanto (SAGACITY : Journal of Theology and Christian Education, 2023)
Abstract.Awareness of God is a religius base for human’s faith in the middle of human’s life development that keep moving forwards progressively. The Old Testament gives stories about human’s struggling in understanding and knowing God’s existency in realms. God is real and presence in every aspects of human’s life. This article will give contribution to get better understanding in knowing the progress of awareness of God from time to times until nowadays.